Big data and its impact on the 3Rs: a home cage monitoring oriented review - Fuochi, Sara; Rigamonti, Mara; O'Connor, Eoin C.; De Girolamo, Paolo; D'Angelo, Livia (Frontiers in Big Data, 2024)
Undisturbed home cage recording of mouse activity and behavior has received increasing attention in recent years. In parallel, several technologies have been developed in a bid to automate the data collection and interpretation. Thanks to these expanding technologies, massive data sets can be recorded and saved in the long term, providing a wealth of information with regards to animal wellbeing, clinical status, baseline activity and subsequent deviations in case of experimental interventions. Such large data sets can also serve as a long-term reservoir of scientific data that can be reanalyzed and repurposed upon need. In this review, we present how the impact of Big Data deriving from home cage monitoring (HCM) data acquisition, particularly through Digital Ventilated Cages (DVCs), can support application of the 3Rs, by enhancing Refinement, Reduction and even Replacement of research in animals.